The portrait of autism language disorder of Indonesian students (linguistics study) - Wanda Nurul Farihat; Chairuddin (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
Nowadays, the study of autism children is phenomenal but actually it needs deep analysis of the autism children’s language process. This research focuses on the autism children because the children has special character than another human. The autism children’s problem or needs in language then analyze by doing some observations. Language disorder itself become the main problem on autism children. From that reason the researcher uses the portrait of autism language disorder using linguistics study to studied. This research is qualitative descriptive to gain the valid data. In addition, the researcher applies the theory of language disorder to conduct the research. The researcher also uses video which is taken by researcher and show the process of autism children when process the language. Furthermore, the researcher is analysing category of language disorder. Afterwards, the researcher observes any problem in the autism children language from linguistik study. Then researcher conclude the analysis of the study. In the end, the researcher hope the reader can gain any good information from this research.